Rancang Bangun Sistem Pengajuan Cuti Karyawan Pada BPJS Ketenagakerjaan Cabang Kota Medan Menggunakan Metode Waterfall - Suendri; Fikri Aditya Sitorus; Fahmi Zahary (CV. ITTC INDONESIA, 2023)
Each agency has its own regulations for each employee to improve discipline and provide comfort to employees in order to improve the quality of the relevant agency. Every employee has the right to leave at their respective places of work. Leave can be used for employees not working for certain reasons such as personal needs, illness or other needs. Therefore, a web-based information system will be designed for employees to apply for leave. The system design uses a waterfall system development method which consists of several stages starting from analysis, design, implementation, testing and maintenance. So, the implementation of this method produces an information system that meets the system requirements of the agency. By designing this web-based information system, it produces a system that is useful for employees in agencies to apply for leave, so that leave applications can be more efficient and have more integrity.